Tinjauan Yuridis Mengenai Inkonsistensi Pengaturan Hukum Tentang Kewenangan KPK dan Polri Dalam Proses Penyidikan Tindak Pidana Korupsi - Maulana, Adam (Fakultas Hukum Universitas Kanjuruhan Malang, 2014)
In Indonesia, corruption has been inhibiting the national growth in various sectors. Regulations concerning corruption are already sharp but the corruptor has not learned any lesson. Both KPK and National Police have legal authority in a corruption investigation. Yet, there is an overlapping element in the regulation authority, resulting in a feud between the KPK and the National Police in the investigation stage.Â Â Â Â Â Â Â Â Â Â Â Based on the above, this study raised the research problem, namely, how the legal arrangements between the KPK and the National Police authorities in the investigation of corruption, and how alternative legal arrangements between them in the investigation of corruption. The benefits are to provide an understanding of the consistency of law enforcement of corruption.Â Â Â Â Â Â Â Â Â Â Â Type of this study is a normative legal research using law approach and legal systems comparison. Types of legal materials in this study obtained from primary legal materials, secondary and tertiary legal materials that were collected by the documents and literature studies. The method of legal materials analysis received from theological and systematic interpretation.Â Â Â Â Â Â Â Â Â Â Â From the results of the research using the method above, it is found that the investigations of corruption by the KPK is based on Law No. 30 of 2002 concerning KPK, while the National Policeâs investigation is based on the KUHAP Juncto law No. 2 of 2002 about Police Juncto and Presidential Instruction No. 5 of 2004 about acceleration of the corruption eradication. Meanwhile, the alternative arrangements investigation is that KPK is authorized to conduct investigations of corruption exceeds the value of Rp 1 billion, and the National Police is given an authorized investigation and inquiries with corruption values less than Rp 1 billion .Â Â Â Â Â Â Â Â Â Â Â Based on the research results, it can be concluded that essentially KPK and National Police has the formal authority to do investigation of corruption. Then, there should be established a specific regulation arrangements about who is entitled to conduct law enforcement investigations and regulates the boundaries of each authority in the investigation of corruption.